Pilot your organization using cash flow planning with frequent feedback - Ottosson, Stig
Based on action research in a small Swedish enterprise conducted over some eighteen months, a major financial activity to combat liquidity shortage consists of weekly cash flow planning with frequent feedback. A model for continuous liquidity planning has been derived from this research.
For enterprises which are growing, developing products or facing tough competition, cash flow is often a limiting factor which determines their success or failure. This article is based on action research in a small enterprise with liquidity shortage whose sales grew at a rate of 20 percent while R&D amounted to 15 percent and profits to 8 percent of turnover. From the investigation it appeared that the most important managing/financial activity consisted of weekly cash flow planning with frequent feedback. Discrepancies between estimates and outcomes suggested what action was to be taken. Some benefits of continuous liquidity planning include better knowledge of revenue and expenses, better total quality, greater personnel involvement, better liquidity, smaller inventory, better earning capacity, and so forth. In the article a model for continuous liquidity planning is presented, based on the study's findings.
Keywords: Cash flow planning